KNOWLEDGE SHARING CAPABILITY, ABSORPTIVE CAPACITY, AND INNOVATION CAPABILITY: AN EMPIRICAL STUDY OF INDONESIA’S INFORMATION AND COMMUNICATION TECHNOLOGY INDUSTRY (Journal of Information and Communication Technology, 2009)
This research investigates the relationships between knowledge sharing capability, absorptive capacity, and innovation capability. This research proposed and tested three hypotheses. The data was collected by conducting a survey on 114 companies of Indonesia’s information and communication technology industry, including a telecommunication service provider, a support service provider, network vendors, and consumer devices vendors. This study finds that absorptive capacity is the intervening factor between knowledge sharing capability and innovation capability. It also shows that potential absorptive capacity has a positive influence on realized absorptive capacity, and realized absorptive capacity has a positive influence on product and process innovation capability.